2019
DOI: 10.1021/acschemneuro.9b00010
|View full text |Cite
|
Sign up to set email alerts
|

DCPIB, an Inhibitor of Volume-Regulated Anion Channels, Distinctly Modulates K2P Channels

Abstract: K2P potassium channels stabilize the resting membrane potential in nearly all cells and have been implicated in several neuronal, cardiovascular, and immune diseases. DCPIB, a known specific and potent inhibitor of volume-regulated anion channels (VRAC), has been reported to activate TREK1 and TREK2 in astrocytes and in vitro recently. In the present study, we demonstrated DCPIB also voltage dependently activated TRAAK besides TREK1/TREK2, showing DCPIB activated all TREK subfamily members. In contrast, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…As with any such another key point raised by our findings is that the current array of VRAC inhibitors are not sufficiently selective for this purpose. Indeed, we and others have demonstrated extensive undesirable off-target activity in even the current gold-standard inhibitor, DCPIB (Afzal et al, 2019;Lv et al, 2019;Minieri et al, 2013). As such, the discovery of compounds with greater selectivity for VRAC over other chloride channels would be of great benefit, both to better understand VRAC's roles in physiology and to explore its value as a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…As with any such another key point raised by our findings is that the current array of VRAC inhibitors are not sufficiently selective for this purpose. Indeed, we and others have demonstrated extensive undesirable off-target activity in even the current gold-standard inhibitor, DCPIB (Afzal et al, 2019;Lv et al, 2019;Minieri et al, 2013). As such, the discovery of compounds with greater selectivity for VRAC over other chloride channels would be of great benefit, both to better understand VRAC's roles in physiology and to explore its value as a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported an impairment of proliferation and/or migration of various cell lines in the presence of VRAC inhibitors [24,25,28,29,30,31,32,33,34,35,36,37,38]. However, the available VRAC inhibitors display little selectivity and often also inhibit other anion channels [55,56], or as in the case of the potent and relatively selective VRAC blocker DCPIB [57] even modulate potassium channels [58,59]. The identification of LRRC8 proteins as essential VRAC components [4,5] enabled investigating physiological functions of VRAC by molecular biological tools.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, DCPIB is unable to cross the blood–brain barrier when administered intravenously and suffers from poor selectivity (Zhang et al, ) DCPIB inhibits VRAC activity with an IC 50 of approximately 5 µM, making it the most potent and best‐in‐class VRAC inhibitor currently available. However, at concentrations used to inhibit VRAC, DCPIB also inhibits H‐K‐ATPase (Fujii et al, ), inward rectifier potassium (Kir) channels (Deng, Mahajan, Baumgarten, & Logothetis, ), two pore‐domain potassium (K2P) channels (Lv et al, ), glutamate release via connexin hemichannels (Bowens, Dohare, Kuo, & Mongin, ), and glutamate uptake by GLT‐1 glutamate transporters (Bowens et al, ). Indeed, the molecular pharmacology of VRAC is plagued by weak and non‐selective inhibitors.…”
Section: Introductionmentioning
confidence: 99%